Efficacy predictors of lung volume reduction with Zephyr valves in a European cohort - Herth, Felix (The European respiratory journal, 2012)
The Endobronchial Valve for Emphysema Palliation Trial (VENT) was a multi-centre, prospective, randomised, controlled trial conducted to evaluate the safety and effectiveness of unilateral endobronchial valve (EBV) treatment. The purpose of this analysis was to assess outcomes in the previously unreported European VENT study cohort. Patients with advanced emphysema were randomly assigned (2:1) to receive Zephyr® (Pulmonx Inc., Redwood City, CA, USA) EBV treatment (n=111) or medical management (n=60). At 6 months, EBV patients demonstrated a significant improvement compared with the controls for mean±sd change in forced expiratory volume in 1 s (7±20% versus 0.5±19%; p=0.067), cycle ergometry (2±14 W versus -3±10 W; p=0.04) and St George’s Respiratory Questionnaire (-5±14 points versus 0.3±13 points; p=0.047). At 12 months, the magnitude of the difference between groups for change from baseline was of similar magnitude to the differences seen at 6 months. Rates for complications did not differ significantly. EBV patients with computed tomography (CT) scans suggestive of complete fissure and lobar occlusion had a mean±sd lobar volume reduction of -80±30% and >50% met minimal clinical difference thresholds. The degree of emphysema heterogeneity did not preclude excellent outcomes. Unilateral lobar volume reduction using EBV treatment is safe and superior clinical results correlated with CT suggestive of complete fissures and successful lobar occlusion. Emphysema heterogeneity was not critical for determining positive outcomes.
Gesehen am 11.06.2018
Published online May 31, 2012